PENGARUH CUSTOMER VALUE TERHADAP CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY SEBAGAI STRATEGI MENUJU BISNIS BERKELANJUTAN PADA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI - Eko Retno Indriyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2016)
Customer value is important factors that influence sustainable businses both real sector and service sector. This research ia aimed to examine and analysis the relationship among customer value, customer satisfaction and customer loyalty. This stydi was conducted at Economic and Business Facutlty of Trisakti University which took 180 student as respondents. Using Structural Equation Model, the result shows dimension service value and relationship value of customer value have significant positive influence to customer satisfaction, while dimension core value product of customer value has no significant influence to customer satisfaction. Customer Satisfacation has positive significant influence to Customer Loyalty, only dimension core of value of customer value has significant positive influence to Customer Loyalty while dimension of service value and relationship value have no significant positive influence to customer loyalty.